EDIBLE VACCINES: FUTURE AND ITS PROSPECTS (International Journal of Ayurveda and Pharma Research, 2015)
Vaccines were the result of trial and error research until molecular biology and genetic engineering made possible the creation of many new and improved vaccines. New vaccines need to be inexpensive, easily administered, and capable of being stored and transported without refrigeration; without these characteristics, developing countries find it difficult to adopt vaccination as the central strategy for preventing their most devastating diseases. Edible vaccines hold great promise as a cost-effective, easy-to-administer, easy-to-store, fail-safe and socio culturally readily acceptable vaccine delivery system, especially for the poor developing countries. It involves introduction of selected desired genes into plants and then inducing these altered plants to manufacture the encoded proteins. Introduced as a concept about a decade ago, it has become a reality today. A variety of delivery systems have been developed. Initially thought to be useful only for preventing infectious diseases, it has also found application in prevention of autoimmune diseases, birth control, cancer therapy, etc. Edible vaccines are currently being developed for a number of human and animal diseases. There is growing acceptance of transgenic crops in both industrial and developing countries. Resistance to genetically modified foods may affect the future of edible vaccines. Plants are capable of producing recombinant antigens that undergo similar post translational modifications as their mammalian-derived counterparts and in contrast to bacterial expression systems.